Isu Gender dalam Perspektif Hukum Adat Dalihan Natolu dan Hukum Islam di Padanglawas - Akhirani Nasution, Nur Hakima; Harahap, Erwin (UNES Law Review, 2023)
Indonesia is a country that has a very varied cultural style and has its own characteristics which are able to give birth to customs as a richness of multicultural traditions, one of which is the Dalihan Notolu Customary Law which is based on the principles of Islamic law. The research carried out aims to determine gender issues according to customary law and lihan notolu from the perspective of Islamic law. The approach used uses a mixed method approach with explanatory design. The data collected in the research process consists of primary data and secondary data which are processed through a data triangulation process. The instruments used are questionnaires, interviews, questionnaires which are divided into several sub-indicators which are first tested for their level of validity and level of reliability. Next, a Mancova test was carried out to see the influence and interrelationship of customary law in a perspective based on Islamic rules and law, and the results of the research revealed that gender issues in the perspective of Dalihan Notolu Customary Law and Islamic Law are interrelated and influence each other in creating a very unique social order in society. and does not conflict with the principles of Islamic law